2016
DOI: 10.1136/bjsports-2016-097152
|View full text |Cite
|
Sign up to set email alerts
|

Calculating acute:chronic workload ratios using exponentially weighted moving averages provides a more sensitive indicator of injury likelihood than rolling averages

Abstract: These findings demonstrate that large spikes in workload are associated with an increased injury risk using both models, although the EWMA model is more sensitive to detect increases in injury risk with higher ACWR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
185
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(204 citation statements)
references
References 30 publications
17
185
0
2
Order By: Relevance
“…We reproduce the ACWR methodology for each of the 12 workload features used in our study, using the ACWR groups suggested by Murray et al [26]. They compute the ACWR for a set of (high); (5) ACWR > 2.00 (very high).…”
Section: S2 Appendix the Acwr Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reproduce the ACWR methodology for each of the 12 workload features used in our study, using the ACWR groups suggested by Murray et al [26]. They compute the ACWR for a set of (high); (5) ACWR > 2.00 (very high).…”
Section: S2 Appendix the Acwr Methodsmentioning
confidence: 99%
“…Then, the injury likelihood (IL) is estimated in every ACWR group as the ratio between the number of players who get injured after the training session assigned to that ACWR group and the number of players who do not. Murray et al [26] observe that players whose training sessions result in ACWR > 2 have a higher injury risk than the players in the other groups (i.e., a high IL). In contrast with the literature, we do not find any individual training session resulting in ACWR > 2 (see S2 Fig), while we observe that players whose individual training sessions result in ACWR < 1 have the highest injury risk (S2 Fig).…”
Section: S2 Appendix the Acwr Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common timeframe used was a 1-week acute training load and 4-week chronic training load. [9][10][11]17,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Other timeframes included a 3-day acute load and a 21 daychronic load, 19 or varying timeframes. [37][38][39][40] One study examined various timeframes for calculating ACWR, 37 utilizing 2-9 days for acute loads, and chronic loads varying from 14 to 35 days, while the other study ranged from 1 to 2 weeks for acute loads, and 3-8 weeks for chronic loads, but only utilized the 1:4 week ratio for relationship to injury.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[37][38][39][40] One study examined various timeframes for calculating ACWR, 37 utilizing 2-9 days for acute loads, and chronic loads varying from 14 to 35 days, while the other study ranged from 1 to 2 weeks for acute loads, and 3-8 weeks for chronic loads, but only utilized the 1:4 week ratio for relationship to injury. 38 Five studies utilized exponentially weighted moving averages (EWMA) for their calculation of ACWR 17,27,29,36,39 and four articles studied a combination of ACWR and chronic workload. 11,30,38,39 Lastly, one study examined ACWR in combination with recent lower limb injuries, 36 while another evaluated the effects of fitness on the relationship between ACWR and injury risk.…”
Section: Study Characteristicsmentioning
confidence: 99%